Method for assessing contaminant migration in tailings fill
Patent Information
- Application Number
- CN202611144507.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-07-30
AI Technical Summary
其二,在污染源强的获取方式上,上述方法均依赖于常规实验环境下的短期测试数据,无法反映充填体中污染物在数十年乃至更长时间尺度下的长期释放行为
1、本申请提供了一种评估尾矿充填体中污染物迁移的方法,首次将超重力离心模型试验技术应用于尾矿充填体污染物迁移测试领域。利用超重力场的缩时效应(时间相似比为1/n2),在实验室条件下将长达数十年的污染物迁移过程压缩至数小时内完成测试,克服了常规物理模型试验时间尺度不匹配、无法在合理周期内获得长期迁移规律的技术难题。
Smart Images

Figure CN122671297B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of materials testing and analysis technology, and in particular to a method for assessing the migration of pollutants in tailings backfill bodies. Background Technology
[0002] Tailings backfilling utilizes tailings as backfill aggregate in underground goaf areas, representing a fundamental path for the large-scale, resource-based, and comprehensive disposal of tailings. However, tailings commonly contain toxic and harmful components such as heavy metals, metalloids, and sulfides. During the construction of backfill bodies using tailings, factors such as the ore beneficiation process, the tailings' harmless treatment process and the properties and quantity of the resulting precipitates, the sulfur content in the tailings (pyrite, pyrrhotite, chalcopyrite), the initial pH value, the performance and ratio of the cementing agent, water saturation, and the environment of the backfilling area all play a crucial role in the strength of the backfill and the migration patterns of pollutants. In particular, the stability of the backfill is affected by the sulfide and sulfate content, curing time, and the type and proportion of the binder material. Specifically, the expansion phase generated by sulfate erosion can lead to the formation of cracks within the backfill, thereby increasing oxygen migration to individual particles and accelerating the migration of pollutants to groundwater. Sulfates in tailings backfill can originate from sulfide oxidation, gypsum dissolution, cyanide leaching, tailings treatment processes, and the binder itself. Therefore, there is an urgent need to develop assessment methods that can scientifically evaluate the strength of tailings backfill in underground environments and the long-term migration and transformation patterns of pollutants, providing technical support for the environmental safety management of tailings backfill utilization.
[0003] The key constraint on the widespread application of tailings backfilling technology lies in its long-term environmental risks to groundwater. Because the strength decay of the backfill and the migration and release of pollutants are extremely slow, often lasting for decades or even longer, accurate prediction becomes exceptionally difficult. In any risk assessment method, determining the source strength of pollutants is the most crucial and fundamental step. If the source strength data lacks representativeness, the reliability of subsequent assessment results will be significantly compromised.
[0004] Patent application CN 117407944 A discloses a GMS-integrated GIS method for predicting the health risks of groundwater in open-pit mine backfill. This method determines the intensity of pollution sources by conducting static leaching tests on backfill materials.
[0005] Patent application CN 119849775 A discloses a risk assessment method and apparatus for solid waste backfilling. The method involves conducting column leaching experiments on solid waste filler samples for backfilling to obtain leaching curves, and determining the leaching concentration of pollutants of interest accordingly.
[0006] The aforementioned existing technologies share two common limitations: First, both methods are designed for risk assessment and prediction in open-pit tailings backfilling scenarios, lacking assessment for underground backfilling scenarios. Second, regarding the acquisition of pollution source strength, the methods rely on short-term test data under conventional experimental conditions, failing to reflect the long-term release behavior of pollutants in the backfill over decades or even longer timescales.
[0007] In summary, there is currently a lack of experimental methods that can accurately simulate and test the contaminant migration behavior of downhole packings during long-term service. Summary of the Invention
[0008] To address the shortcomings of the existing technology, the purpose of this application is to provide a method for assessing the migration of pollutants in tailings backfill. This method utilizes the time-lapse and scale-down effect under hypergravity to effectively test the long-term transport patterns of pollutants after underground backfilling of tailings backfill, providing reliable experimental data support for the long-term environmental risk assessment of tailings backfill.
[0009] To achieve the above-mentioned objectives, this application provides a method for evaluating the migration of pollutants in tailings backfill, wherein the tailings backfill to be tested is placed in a model test apparatus for testing; the model test apparatus includes a test chamber, a model box disposed within the test chamber, and an effluent collection device. The model box is a cuboid with an open top, used to hold tailings backfill samples; The model box is equipped with two movable partitions that are arranged opposite each other along the extension direction of the long sidewall; the two short sidewalls of the model box are provided with threaded holes and bolts for pushing the movable partitions. The outflow collection device includes a collection bottle, and a first orifice pressure gauge is provided at the bottom of the collection bottle; The method for assessing the migration of pollutants in tailings backfill includes the following steps: Based on the actual size of the goaf and the preset hypergravity acceleration, the geometric dimensions of the tailings backfill sample are calculated, and the tailings backfill sample is prepared. An HDPE membrane was laid inside the model box as a seepage-proof lining. After uniformly applying sealant to the bottom surface and two short sides of the tailings backfill sample, it is placed inside the model box. The bolts on both sides are rotated to push the movable partition until it abuts against the short sides of the tailings backfill sample. Then, sealant is filled between the movable partition and the short sidewall of the model box, so that two isolated and unconnected upstream and downstream water tanks are formed on both sides of the tailings backfill sample. A water inlet is provided on the long sidewall of the model box near the upstream water tank, and an overflow hole is provided on the long sidewall near the downstream water tank. Cover the model box with the lid and seal the joint between the lid and the box with sealant. The upstream water tank is connected to the Marshall bottle, and a second manometer is installed at the bottom of the Marshall bottle. The water outlet of the Marshall bottle continuously replenishes the upstream water tank through the water inlet. The upstream water head is set by adjusting the suspension height of the Marshall bottle. The water from the overflow hole of the downstream water tank is introduced into a collection bottle through a pipeline for collection. One or more model boxes and outflow collection devices are placed inside the test chamber, and the test chamber is filled with sand to obtain the assembled test chamber; The first and second orifice manometers are connected to the host computer via signal transmission. Check the sealing performance of the model box: The Marsh bottle was lifted to a preset height H1 using a crane. After the seepage stabilized, the water output of the collection bottle per unit time was measured, and the permeability coefficient k of the tailings backfill sample was calculated based on the water output. The permeability coefficient k is compared with the known range of permeability coefficients of tailings backfill samples: if the value of k is on the same order of magnitude as the permeability coefficient of the tailings backfill samples, the sealing performance of the model box is determined to meet the test requirements; otherwise, it indicates that there is a sealing defect in the model box, and it needs to be resealed and the sealing performance is tested again after the treatment, until the measured permeability coefficient k value is on the same order of magnitude as the permeability coefficient of the tailings backfill samples. Pollutant migration test: The assembled test chamber was placed in a centrifuge and continuously operated in a centrifugal field with a preset acceleration of ng. During the entire operation, the outflow rate of the water in the collection bottle was monitored in real time using the first orifice manometer located at the bottom of the collection bottle, and the change over time was recorded. During the operation under hypergravity, water samples are collected at preset time intervals, and the content of pollutants in the water samples is detected to analyze the migration and release patterns of pollutants in the filling body. After the hypergravity operation is completed, stop the machine and remove the test chamber; The model box was disassembled and samples were taken. During sampling, three samples were collected evenly along the thickness direction of the tailings backfill sample from the upstream, middle and downstream layers, respectively, for a total of nine samples. The content of residual pollutants in the samples was detected, and the migration and release patterns of pollutants in the backfill were analyzed in combination with the effluent test results.
[0010] Furthermore, the method for determining the size of the tailings backfill sample is as follows: In a pre-set hypergravity field with an acceleration of ng, the geometric characteristic dimension L of the tailings backfill sample is determined. c The actual size L of the goaf k The following relationship exists between them: L c =L k / n; Where n is the multiple of the supergravity acceleration.
[0011] Furthermore, the method for determining the placement height of the Marshall bottle is as follows: the vertical difference between the bottom height of the Marshall bottle's air inlet pipe and the overflow hole is equal to the preset head difference ΔH. The head difference ΔH satisfies the following relationship: ΔH = D × J; Where D is the thickness of the tailings backfill sample, and J is the hydraulic gradient of the goaf.
[0012] Furthermore, when checking the sealing performance of the model box, the preset height H1 of the Marshall bottle is calculated as follows: H1 = H2 + ΔH; where H2 is the height of the overflow orifice and ΔH is the head difference.
[0013] Furthermore, the formula for calculating the permeability coefficient k is as follows: k = V × D / (A × ΔH × t); Where V is the outflow rate of the collection bottle measured by the first pore pressure gauge, D is the thickness of the tailings backfill sample, A is the cross-sectional area of the tailings backfill sample, ΔH is the head difference, and t is the seepage time.
[0014] Furthermore, the tailings in the tailings filling samples were sourced from gold tailings, non-ferrous metal tailings, ferrous metal tailings, red mud, phosphogypsum, or coal gangue.
[0015] Furthermore, the tailings backfill sample is a cemented backfill, a paste-like backfill, a paste backfill, a non-cemented dry backfill, or a backfill modified with additives.
[0016] Furthermore, the tailings backfill sample is a cemented backfill, and the cementing material in the cemented backfill is selected from at least one of cement, slag, fly ash, gypsum, lime, and polymer cementitious agents.
[0017] The beneficial effects of this application are as follows: 1. This application provides a method for evaluating the migration of contaminants in tailings backfill bodies, and for the first time applies the hypergravity centrifugation model test technology to the field of contaminant migration testing in tailings backfill bodies. It utilizes the time-shortening effect of the hypergravity field (time similarity ratio of 1 / n). 2 This technology compresses the decades-long pollutant migration process into a few hours under laboratory conditions, overcoming the technical challenge of mismatched time scales in conventional physical model experiments and the inability to obtain long-term migration patterns within a reasonable period.
[0018] 2. The method for assessing pollutant migration in tailings backfill provided in this application recreates the actual service environment of the backfill, and the test results are closer to engineering practice. Furthermore, by establishing a closed-loop sealing inspection process of "inspection—judgment—resealing," the reliability and repeatability of the test data are effectively guaranteed.
[0019] 3. The method for assessing pollutant migration in tailings backfill provided in this application establishes a multi-parameter dynamic monitoring system, ensuring the safe operation of the device under hypergravity conditions. By installing a second manometer at the bottom of the upstream Marvin bottle and a first manometer at the bottom of the downstream collection bottle, continuous and dynamic monitoring of the influent and effluent flow rates during hypergravity operation is achieved. Combined with the timed collection and testing of effluent samples during operation and the sampling and testing of residual pollutants in the samples after shutdown, a three-in-one data acquisition system of "flow rate-concentration-residue" is formed, providing complete experimental data support for the multi-dimensional analysis of pollutant migration patterns. In addition, by setting up multiple protective structures inside the test chamber (Marvin bottle isolation protection, independent protective space for the collection bottle, unsaturated sand lateral support, etc.), the structural stability and operational safety of the device under the high-speed operation conditions of the hypergravity centrifuge are fully guaranteed. Attached Figure Description
[0020] Figure 1 This is a top view of the model box in this application without the cover plate.
[0021] Figure 2 This is a cross-sectional view of the short sidewall of the model box in this application.
[0022] Figure 3 This is a cross-sectional view of the model box along the long sidewall direction in this application.
[0023] Figure 4 This is a schematic diagram of the model box and outflow collection device in this application.
[0024] Figure 5 This is a cross-sectional schematic diagram of the test chamber in this application.
[0025] Figure 6 This is a schematic diagram of the sampling locations in this application.
[0026] Figure 7 XPS As 3d fine spectroscopic analysis of the raw ore and cyanide slag III in Example 1; where A is the raw ore and B is the cyanide slag III.
[0027] Figure 8The images show the upstream and downstream surfaces of the cyanide slag backfill sample 1, cyanide slag backfill sample 2, and cyanide slag backfill sample 3 after the transfer process. Among them, A and D are the upstream and downstream surfaces of the cyanide slag backfill sample 1, respectively; B and E are the upstream and downstream surfaces of the cyanide slag backfill sample 2, respectively; and C and F are the upstream and downstream surfaces of the cyanide slag backfill sample 3, respectively.
[0028] Explanation of reference numerals in the attached figures: 100. Tailings backfill sample; 1. Downstream water tank; 2. Sealant; 3. HDPE membrane; 5. Movable partition; 6. Model box; 7. Bolt; 8. Sealant; 9. Sand; 10. Overflow hole; 11. Upstream water tank; 12. Water inlet; 13. Air inlet pipe; 14. Marvi bottle; 15. Collection bottle; 16. First orifice manometer; 17. Collection bottle rack; 18. Second orifice manometer; 19. Test chamber; 20. Aluminum alloy partition. Detailed Implementation
[0029] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0031] Hypergravity experiments are a physical model testing method that uses centrifugal acceleration to simulate hypergravity fields. Through scaling and time-lapse effects, it is possible to reproduce long-duration, large-scale evolution processes in actual engineering on a laboratory scale. The hypergravity field is generated by a centrifuge. The model is placed in the experimental chamber at the end of the centrifuge arm at high speed, subjecting the model to centrifugal acceleration much greater than that of gravity, thereby increasing the volume forces of the model and compensating for the stress loss due to the model's scaling.
[0032] Compared with physical simulation under normal gravity conditions, the core advantages of hypergravity experiments are reflected in two aspects: scaling effect and time-lapse effect. (1) Scale effect. In a normal gravity field, the stress inside the scaled model is lower than that of the prototype, and it cannot reflect the stress level of the prototype. In a hypergravity field, if the scale ratio of the model is 1 / N, applying a centrifugal acceleration of Ng to it can make the self-weight stress of the model consistent with that of the prototype, thereby reproducing the stress field and hydraulic field of the large-scale prototype on the scaled model. (2) Time-lapse effect. The hypergravity field increases the relative driving force between different phase substances, accelerates the migration speed of fluids and solutes in the model, thereby simulating the long-term migration process of solutes or pollutants in the prototype in a short time. Taking a 100 g gravitational acceleration as an example, a model test of only 43.8 hours can simulate the migration process of the prototype for up to 50 years.
[0033] Please see Figures 1 to 6 As shown, this application provides a method for evaluating the migration of pollutants in tailings backfill, wherein the tailings backfill to be tested is placed in a model test device for testing; wherein the model test device includes a test chamber 19, a model box 6 disposed in the test chamber 19, and an outflow collection device.
[0034] Among them, the model box 6 is a cuboid with an open top, used to place the tailings backfill sample 100.
[0035] The model box 6 is equipped with two movable partitions 5 arranged opposite each other along the extension direction of the long sidewall; the two short sidewalls of the model box 6 are provided with threaded openings and bolts 7. By turning the bolts 7, they are pushed inward through the threaded openings to push the movable partitions 5 into the box, thereby applying controllable lateral pressure to the two short sides of the tailings backfill sample 100 that is subsequently filled, and improving the sealing of the sample sides.
[0036] The outflow collection device includes a collection bottle 15 connected to the overflow hole 10, and a first orifice gauge 16 is provided at the bottom of the collection bottle 15.
[0037] The method for assessing the migration of contaminants in tailings backfill includes the following steps: Based on the actual size of the goaf and the preset hypergravity acceleration, the geometric dimensions of the tailings filling sample were calculated, and a tailings filling sample 100 was prepared.
[0038] Specifically, the dimensions of the tailings backfill sample 100 are strictly determined according to the scaling similarity law of the hypergravity field. In a hypergravity field with a preset acceleration of ng, the sample and the goaf satisfy the geometric similarity condition, i.e., the geometric characteristic dimension L of the sample... c Compared with the actual size L of the goaf k The following relationship exists between them: L c =L k / n; Where n is the multiple of hypergravity acceleration, this scaling relationship can be used to reduce the large-scale field-filled structure to a laboratory-scale physical specimen.
[0039] Among them, the tailings of the tailings filling samples are gold tailings, non-ferrous metal tailings, ferrous metal tailings, red mud, phosphogypsum or coal gangue.
[0040] The tailings backfill samples were cemented backfill, paste-like backfill, paste backfill, non-cemented dry backfill, or backfill modified with additives.
[0041] When the tailings backfill sample is a cemented backfill, the cementing material in the cemented backfill is selected from at least one of cement, slag, fly ash, gypsum, lime, and polymer cementitious agents.
[0042] Since the tailings backfill sample 100 can be regarded as a non-deformable solid medium during the test, the pollutant migration measurement can be carried out after the tailings backfill sample 100 and the model box 6 are sealed and assembled.
[0043] HDPE membrane 3 is used as an impermeable lining and is laid tightly against the inner wall of model box 6, so that model box 6 can safely store water containing toxic components.
[0044] After uniformly applying sealant 8 to the bottom surface and two short sides of the tailings backfill sample 100, it is placed inside the model box 6. The bolts 7 on both sides are rotated to push the movable partition 5 until it abuts against the short sides of the tailings backfill sample 100. Subsequently, sealant 2 is filled between the movable partition 5 and the short sidewall of the model box 6 to seal the area, forming two isolated and unconnected upstream and downstream water tanks 11 and 1 on both sides of the tailings backfill sample 100. A water inlet 12 is provided on the long sidewall of the model box 6 near the upstream water tank 11, and an overflow 10 is provided on the long sidewall near the downstream water tank 1.
[0045] Cover the model box 6 with the lid and seal the seam between the lid and the box with sealant.
[0046] The upstream water tank 11 is connected to the Marshall bottle 14. A second manometer 18 is installed at the bottom of the Marshall bottle 14. The water outlet of the Marshall bottle 14 continuously replenishes the upstream water tank 11 through the water inlet 12. The upstream water head is set by adjusting the suspension height of the Marshall bottle 14.
[0047] Specifically, the height of the Marsh bottle 14 is determined based on the required head difference ΔH. The specific adjustment method is as follows: the vertical difference between the bottom of the air inlet pipe 13 of the Marsh bottle 14 and the overflow hole 10 is equal to the preset head difference ΔH. The head difference ΔH satisfies the following relationship: ΔH = D × J; Where D is the thickness of the tailings backfill sample, and J is the hydraulic gradient of the goaf.
[0048] The water from the overflow hole 10 of the downstream water tank 1 is introduced into the collection bottle 15 through the pipeline for collection. A first orifice gauge 16 is placed at the bottom of the collection bottle 15.
[0049] The first orifice manometer 16 and the second orifice manometer 18 are connected to the host computer via signal.
[0050] In some embodiments, the collection bottle 15 is a capped HDPE pressure-resistant vacuum bottle.
[0051] The first orifice manometer 16 is a pore water manometer. The principle of flow monitoring is as follows: as water continuously flows from the overflow orifice 10 into the collection bottle 15, the water level in the collection bottle 15 gradually rises, resulting in a corresponding increase in the static water pressure at the bottom of the bottle; the first orifice manometer 16 converts the real-time collected static water pressure signal into an electrical signal and transmits it back to the host computer in the control room, thereby realizing dynamic and indirect monitoring of the outflow rate.
[0052] The second pore pressure gauge 18 is a pore water pressure gauge. The principle of flow monitoring is as follows: as the water from the overflow hole 10 continues to flow into the collection bottle 15, the water level in the Marshall bottle 14 gradually decreases, resulting in a corresponding decrease in the static water pressure at the bottom of the bottle; the second pore pressure gauge 18 converts the real-time collected static water pressure signal into an electrical signal and transmits it back to the host computer in the control room, thereby realizing dynamic and indirect monitoring of the inlet water flow.
[0053] Making test chamber 19: According to the actual needs of the test, one or more model boxes 6 and outflow collection devices are placed in the test box 19, and sand 9 is filled into the test box 19 to obtain the assembled test box.
[0054] Among them, the filling height of sand 9 meets the following requirements: the unsaturated earth pressure generated by it can form effective lateral support for model box 6, thereby resisting the effect of water pressure inside model box 6 on the box wall.
[0055] Check the sealing performance of the model box: A crane was used to lift the Marsh bottle 14 to a preset height H1. After the seepage stabilized, the outflow rate V of the collection bottle 15 per unit time was measured, and the permeability coefficient k of the tailings backfill sample was calculated based on the outflow rate V.
[0056] The calculation method for the preset height H1 of the Marsh bottle 14 when checking the airtightness of the model box is as follows: H1 = H2 + ΔH; where H2 is the height of the overflow orifice 10 and ΔH is the head difference.
[0057] The formula for calculating the permeability coefficient k is as follows: k = V × D / (A × ΔH × t); Wherein, V is the outflow of water from the collection bottle 15 as measured by the first pore pressure gauge 16, D is the thickness of the tailings backfill sample, A is the cross-sectional area of the tailings backfill sample, ΔH is the head difference, and t is the seepage time.
[0058] The permeability coefficient k is compared with the known range of permeability coefficients of tailings backfill samples: if the value of k is on the same order of magnitude as the permeability coefficient of the tailings backfill samples, the sealing performance of the model box is deemed to meet the test requirements; otherwise, it indicates that the model box has a sealing defect and needs to be resealed. After resealing, the sealing performance test is carried out again until the measured permeability coefficient k value is on the same order of magnitude as the permeability coefficient of the tailings backfill samples.
[0059] Pollutant migration test: The assembled test chamber is placed in a centrifuge and continuously operated in a centrifugal field with a preset acceleration of ng. During the entire operation, the flow rate of the water in the collection bottle 15 is monitored in real time using the first orifice manometer 16 located at the bottom of the collection bottle 15, and the change over time is recorded. During the operation under high gravity, water samples are collected at preset time intervals, and the content of pollutants in the water samples is detected to analyze the migration and release patterns of pollutants in the filling body. After the hypergravity operation is completed, stop the machine and remove the test chamber; Model box 6 was disassembled and samples were taken. During sampling, three samples were collected evenly along the thickness direction of the tailings backfill sample from the upstream, middle, and downstream layers, respectively, for a total of nine samples. The content of residual pollutants in the samples was tested to analyze the migration and release patterns of pollutants in the backfill in conjunction with the effluent test results. The sampling locations are as follows: Figure 6 As shown.
[0060] The model box 6, the movable partition 5, and the test chamber 19 are all made of carbon steel, stainless steel, aluminum alloy, manganese steel, titanium, or titanium-steel composite plate.
[0061] It should be understood that, depending on the actual needs of the test, one or more model boxes can be placed side by side or in a predetermined layout within a single test chamber 19 to conduct multi-condition or parallel comparison tests.
[0062] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0063] Example 1 This embodiment provides a method for assessing the migration of pollutants in tailings backfill, including the following steps: Preparation of tailings backfill samples: The gold cyanide tailings (cyanide slag) were used to prepare the backfill material, with cement as the binder and a cement-sand ratio of 1:4.
[0064] Determine the dimensions of the cyanide slag backfill sample: Based on the geometric scaling similarity law of the hypergravity field, under the pre-set hypergravity acceleration of 100 g (n=100), the model and prototype satisfy L... c =L k Similarity relationship of / n.
[0065] In this embodiment, the prototype dimensions of a certain goaf area are 40 m long × 40 m wide × 20 m high. After being scaled down by 100 times, the corresponding dimensions of the cyanide slag backfill sample are determined to be 40 cm long × 40 cm wide × 20 cm high.
[0066] Making the model box: S11. An open container is made of carbon steel plate by welding process, which serves as the main structure of model box 6. The dimensions are 580 mm long × 310 mm wide × 528 mm high. S12. A movable partition 5 (aluminum alloy partition) is installed on the inner wall of each of the two short side walls of the model box 6. The gap between the aluminum alloy partition and the carbon steel plate is filled and sealed with sealant 2. S13. Four threaded openings are reserved on the two short sidewalls and M12 bolts are installed so that the bolts can be screwed through the threaded openings and pushed inward to push the aluminum alloy partition into the box, thereby applying controllable lateral pressure to the two short sides of the subsequently filled cyanide slag backfill sample and improving the sealing of the sample sides. S14. HDPE membrane 3 is used as an impermeable lining and is laid tightly against the inner wall of model box 6 to enable model box 6 to safely store water containing cyanide. S15. After uniformly coating the bottom surface and two short sides of the cyanide slag filling sample with sealant 8, place it into the model box 6 so that the sample forms two isolated and unconnected upstream water tanks 11 and downstream water tanks 1. S16. Install the model box cover and seal the joint between the cover and the box body with sealant; S17. An overflow hole 10 is made on the long side wall of the model box 6 near the downstream water tank 1, 48 cm away from the bottom surface of the model box 6, to determine the downstream water head; that is, the height H2 of the overflow hole 10 is 48 cm.
[0067] S18. The upstream water tank 11 is connected to the Marshall bottle 14. A second orifice gauge 18 is placed at the bottom of the Marshall bottle 14 for dynamic and indirect monitoring of the inlet water flow. A water inlet hole 12 is provided on the long side wall of the model box 6 near the upstream water tank 11.
[0068] Given that the hydraulic gradient of the goaf is 0.276 m / m and the thickness of the cyanide slag backfill sample is 20 cm, the calculated head difference ΔH = D × J = 20 cm × 0.276 m / m ≈ 5.5 cm; the preset height of the Marsh bottle 14 is H1 = H2 + ΔH = 48 cm + 5.5 cm = 53.5 cm.
[0069] That is, under 100 g of hypergravity, the head difference can reach 5.5 m, the upstream head is maintained at 53.5 cm by fixing the height of the Marsh bottle 14, and the water outlet of the Marsh bottle 14 continuously replenishes the upstream water tank 11 through the water inlet 12 of the upstream water tank.
[0070] S19. Water from the overflow hole 10 of the downstream water tank is introduced into the collection bottle 15 through a pipeline for collection. The collection bottle 15 is a capped HDPE pressure-resistant vacuum bottle with a first-hole pressure gauge 16 placed at the bottom. The first-hole pressure gauge 16 and the second-hole pressure gauge 18 are connected to the host computer for signal transmission.
[0071] Making the test chamber: S31. The main structure of the test chamber 19 is made of carbon steel plate by welding process, with dimensions of 1.36 m in length × 1.11 m in width × 1.08 m in height; S32. The outflow collection device includes a collection bottle 15 and a collection bottle rack 17 for placing the collection bottle 15.
[0072] Place the model box 6 and the outflow collection device into the test chamber 19. Set an acrylic plate between the Martens bottle 14 and the adjacent side wall of the test chamber to isolate and protect the Martens bottle 14 and prevent it from being impacted or damaged by external forces during the operation of the centrifuge. S33. Take four aluminum alloy partition plates 20 rings and place them around the collection bottle 15 to separate the space for independently placing the collection bottle 15, so as to prevent the pressure of unsaturated sand under hypergravity environment from causing the collection bottle to deform under pressure. S34. Fill test chamber 19 with sand; S35. Three model boxes were placed side by side evenly in the test chamber 19 to carry out comparative tests on cyanide slag backfill samples (cyanide slag one, cyanide slag two, and cyanide slag three) under different working conditions. The component content of the three cyanide slag backfill samples is shown in Table 1, and the content of pollutants in the toxic leachate of the cyanide slag backfill is shown in Table 2.
[0073] Check the sealing performance of the model box: S41. To verify the airtightness of the model box, a seepage test was conducted under constant gravity with a head difference of 5.5 m, and the permeability coefficient was recorded to determine whether it was within the reasonable range for the cyanide slag backfill test. Since the upstream head of the model box 6 is controlled by the connected Marviate bottle 14, and water is replenished to it, the head difference between the upstream and downstream sides can be controlled simply by adjusting the height of the Marviate bottle 14 and the downstream overflow hole 10.
[0074] A crane was used to lift Marviator 14, and a seepage test was conducted at a height of 5.5 m above the overflow hole of the downstream water tank. The seepage rates of three cyanide slag backfill samples were recorded as 30.82 mL / h, 112.5 mL / h, and 43.26 mL / h, respectively. The calculated permeability coefficients were 2.14 × 10⁻⁶. -9 cm / s, 7.8×10 -9 cm / s, 3×10 -9 cm / s; S42. Consult the empirical values for the permeability coefficient of tailings backfill, which are within the range of 10. -9 ~10 -8 cm / s, the aforementioned permeability coefficient is within this range, indicating that the sealing performance of the model box meets the test requirements.
[0075] Pollutant migration test: S51. Place the assembled test chamber in a centrifuge and run it continuously in a centrifugal field with a preset acceleration of 100 g. Throughout the operation, use the first orifice manometer 16 located at the bottom of the collection bottle 15 to monitor the outflow rate of the water in the collection bottle 15 in real time and record the change over time. S52. During the operation under hypergravity, water samples were collected and pollutant content was tested at 6, 18, 30, 42, and 48 hours, which correspond to 6.8, 20.5, 34.2, 47.9, and 54.8 years under normal gravity (g), respectively, in order to analyze the migration and release patterns of pollutants in the backfill. S53. After the centrifuge operation is completed, stop the centrifuge and remove the test chamber. Disassemble the model chamber and take samples. During sampling, collect three samples evenly along the thickness direction of the cyanide slag backfill sample from the upstream, middle and downstream layers, respectively, for a total of nine samples, which are used to detect the content of residual pollutants.
[0076] The relevant technical specifications of this embodiment are shown in the table below.
[0077] Table 1. Analysis of component content in cyanide slag Table 2. Analysis of pollutants in the toxic leachate of cyanide slag backfill after 28 days of curing (unit: mg / L) Note: The leachate was prepared according to the "Solid Waste Leaching Toxicity Leaching Method - Sulfuric Acid and Nitric Acid Method (HJ / T 299-2007)".
[0078] The data above shows that the pyrite and arsenic content in cyanide slag I is higher than that in cyanide slag II and cyanide slag III. It should be noted that cyanide slag III is obtained by purifying cyanide slag II with ozone.
[0079] Table 3. Analysis of pollutant content in effluent from cyanide slag backfilling bodies (unit: mg / L) Note: The standard is derived from Class III of the Groundwater Quality Standard (GB 14848-2017).
[0080] The data above show that, under 100 g hypergravity conditions, this experiment simulated the migration patterns of pollutants in cyanide slag backfill over a 48-hour (54.8-year) timescale. The results indicate that, except for copper, arsenic, and mercury, all other pollutants were not detected.
[0081] The total arsenic concentration in the effluent from cyanide slag backfill body 1 consistently exceeded the Class III limit in the "Groundwater Quality Standard" (GB 14848-2017); the arsenic concentration in the effluent from cyanide slag backfill body 2 exceeded the standard at 6 and 18 hours, but met the standard requirements at other times; the arsenic concentration in the effluent from cyanide slag backfill body 3 only slightly exceeded the standard at 6 hours, and met the standard requirements at other times. The reason for the variation in arsenic content is that hypergravity significantly enhanced the convection and diffusion rates of water, dissolved oxygen, and reaction products in the pores of the backfill body. Oxygen was transported to the pyrite surface more quickly, accelerating the electrochemical reaction between pyrite and oxygen and water. The reaction process is as follows: 2FeS2 + 7O2 + 2H2O = 2Fe 2+ +4SO4 2- +4H + ; The acid produced by the reaction lowers the pH of the environment, disrupts the stability of the pyrite lattice, and causes a large amount of arsenic that was originally fixed in the lattice to be converted into a soluble state, enters the pore water and migrates with the water flow, ultimately resulting in a significant increase in the arsenic concentration in the effluent.
[0082] Compared to cyanide residue II, cyanide residue III underwent ozone purification treatment. To further analyze the interfacial reaction mechanism between minerals and pollutants during the ozone purification process, a fine spectral scan of the As 3d region (36–51 eV) was performed to further analyze its chemical valence state. The results are as follows: Figure 7 As shown.
[0083] By fitting the data, two main component peaks of As were obtained, namely 47.4 eV and 43.7 eV, corresponding to As(V) and As(III), respectively. The results of integrating the two peaks and calculating their proportions are shown in Table 4.
[0084] Table 4. Peak area ratio of As(V) and As(III) in raw ore and cyanide slag III Analysis revealed that the peak area ratio (As(V) / As(III)) of the cyanide slag group III was higher than that of the original ore, increasing from 0.20 to 0.47. This indicates that the proportion of pentavalent arsenic in the cyanide slag III was higher than that in the original ore. This is because, during the ozone purification process, As(III) on the surface of the cyanide slag group III was oxidized by ozone to form As(V). As(V) is less toxic than As(III), indicating that the ozone purification process not only degraded the cyanide on the surface of the cyanide slag group III but also reduced the arsenic toxicity of the cyanide slag group III through oxidation.
[0085] In subsequent hypergravity experiments, even when As(V) was released from pyrite, its migration behavior changed fundamentally: As(V) was rapidly absorbed by Fe produced from the oxidation of pyrite in the surrounding environment. 3+ The newly formed iron oxides / hydroxides from hydrolysis are strongly adsorbed and effectively fixed on the solid surface, making it difficult for them to enter the main water flow. Therefore, the arsenic concentration in the effluent from the cyanide slag three-stage backfill is significantly lower than that from the cyanide slag two-stage backfill, consistent with the results of the hypergravity test.
[0086] The trend shows that copper and arsenic migrated rapidly in the early stage of backfilling, but as time went on, the rate at which pollutants migrated out of the backfill with groundwater slowed down.
[0087] After the rotation was completed, the model box was disassembled and samples were taken to test the content of residual contaminants in the filling material. The condition of the upstream and downstream surfaces of the three sets of samples after disassembly is as follows. Figure 8 As shown.
[0088] The samples were originally gray, but after the rotation, the surfaces that came into contact with water all turned yellow, and the shape was loose and granular. Compared with the backfill of cyanide slag II and cyanide slag III, the backfill of cyanide slag I was darker in color, orange-yellow, and more loose, with the surface layer damaged and the strength significantly reduced.
[0089] The possible reasons are as follows: The cyanide slag contains iron sulfide, usually existing as pyrite (FeS2) or pyrrhotite (FeS). Upon contact with water, it readily oxidizes to form iron oxide (Fe2O3). The oxidation rate of pyrite is higher under alkaline conditions than under neutral conditions. The hydrated form of iron oxide (Fe2O3•H2O) is yellow, and the cyanide slag 1 filling material, with its higher iron sulfide content, exhibits a darker color. The decreased strength of the cyanide slag 1 filling material is also related to the oxidation reaction of iron sulfide. Firstly, this involves changes in the material system; secondly, the iron sulfide reacts with the cement during the oxidation process, destroying the cement products and causing cracking.
[0090] The oxidation reaction occurs in three steps. First, iron sulfide reacts with water and oxygen to produce iron oxide and sulfuric acid. Then, the iron oxide continues to react to form goethite (FeO(OH)), and some of the goethite further reacts with water to form ferrohydrite (Fe(OH)3). The different substances have different volumes; compared to the volume of pyrite, iron oxide decreases in size. Subsequently, the volume of iron hydroxide increases, exceeding the original volume of iron sulfide. This volume shift creates internal stress that damages the original structure of the infill. The sulfuric acid produced by the oxidation of iron sulfide forms acidic water that continues to react with cement, causing the loss of cement hydration products and hydration gel, leading to structural damage and reduced strength of the infill. Furthermore, the high sulfate content in the cyanide slag causes a sulfate attack reaction with the cementitious materials, as shown in the following equation: Ca(OH)2 + 2SO4 2- + 2H₂O = CaSO₄•2H₂O + 2OH⁻ - Ca4Al2(SO4)(OH) 12 •6H2O + 2SO4 2- + 2Ca 2+ + 20H2O = Ca6Al2(SO4)3(OH) 12 •26H2O; In the above reaction, sulfate first reacts with calcium hydroxide to form gypsum, which then further erodes monosulfide hydrated calcium sulfoaluminate to form ettringite. This process, accompanied by significant volume expansion, leads to cracks inside the infill, increasing oxygen availability and ultimately reducing the strength of the infill.
[0091] Table 5. Analysis of toxic leachate contaminants in the filling material after the turnaround (unit: mg / L) Note: The leachate was prepared according to the "Solid Waste Leaching Toxicity Leaching Method - Sulfuric Acid and Nitric Acid Method (HJ / T 299-2007)".
[0092] The data above show that arsenic and mercury were detected in the toxic leachate of residual pollutants in the backfill after the centrifuge cycle ended. The concentrations of arsenic and mercury in the leachate were higher in the backfill of cyanide slag I than in the backfills of cyanide slag II and cyanide slag III. However, the leachate from all the backfills met the Class III limit in the Groundwater Quality Standard (GB 14848-2017). No other pollutants were detected. This indicates that under 100 g hypergravity conditions, the environmental risk of backfilling under the simulated 48-hour (54.8-year) scale is controllable.
[0093] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A method for assessing the migration of pollutants in tailings backfill, characterized in that, The tailings backfill body to be tested is placed in a model test device for testing; the model test device includes a test chamber, a model box set inside the test chamber, and an outflow collection device; The model box is a cuboid with an open top, used to hold tailings backfill samples; The model box is equipped with two movable partitions that are arranged opposite each other along the extension direction of the long sidewall; the two short sidewalls of the model box are provided with threaded holes and bolts for pushing the movable partitions. The outflow collection device includes a collection bottle, and a first orifice pressure gauge is provided at the bottom of the collection bottle; The method for assessing the migration of pollutants in tailings backfill includes the following steps: Based on the actual size of the goaf and the preset hypergravity acceleration, the geometric dimensions of the tailings backfill sample are calculated, and the tailings backfill sample is prepared. An HDPE membrane was laid inside the model box as a seepage-proof lining. After uniformly applying sealant to the bottom surface and two short sides of the tailings backfill sample, place it in the model box, rotate the bolts on both sides to push the movable partition until the movable partition abuts against the short sides of the tailings backfill sample. Subsequently, sealant is filled between the movable partition and the short sidewall of the model box, so that two isolated and unconnected upstream and downstream water tanks are formed on both sides of the tailings backfill sample; the model box is provided with a water inlet hole on the long sidewall near the upstream water tank and an overflow hole on the long sidewall near the downstream water tank. Cover the model box with the lid and seal the joint between the lid and the box with sealant. The upstream water tank is connected to the Marshall bottle, and a second manometer is installed at the bottom of the Marshall bottle. The water outlet of the Marshall bottle continuously replenishes the upstream water tank through the water inlet. The upstream water head is set by adjusting the suspension height of the Marshall bottle. The water from the overflow hole of the downstream water tank is introduced into a collection bottle through a pipeline for collection. One or more model boxes and outflow collection devices are placed inside the test chamber, and the test chamber is filled with sand to obtain the assembled test chamber; The first and second orifice manometers are connected to the host computer via signal transmission. Check the sealing performance of the model box: The Marsh bottle was lifted to a preset height H1 using a crane. After the seepage stabilized, the water output of the collection bottle per unit time was measured, and the permeability coefficient k of the tailings backfill sample was calculated based on the water output. The permeability coefficient k is compared with the known range of permeability coefficients of tailings backfill samples: if the value of k is on the same order of magnitude as the permeability coefficient of the tailings backfill samples, the sealing performance of the model box is determined to meet the test requirements; otherwise, it indicates that there is a sealing defect in the model box, and it needs to be resealed and the sealing performance is tested again after the treatment, until the measured permeability coefficient k value is on the same order of magnitude as the permeability coefficient of the tailings backfill samples. Pollutant migration test: The assembled test chamber was placed in a centrifuge and continuously operated in a hypergravity field with a preset acceleration of ng. Throughout the entire operation, the flow rate of the water in the collection bottle is monitored in real time using a first-hole manometer located at the bottom of the collection bottle, and the changes over time are recorded. During the operation under hypergravity, water samples are collected at preset time intervals, and the content of pollutants in the water samples is detected to analyze the migration and release patterns of pollutants in the filling body. After the hypergravity operation is completed, stop the machine and remove the test chamber; The model box was disassembled and samples were taken. During sampling, three samples were collected evenly along the thickness direction of the tailings backfill sample from the upstream, middle and downstream layers, respectively, for a total of nine samples. The content of residual pollutants in the samples was detected, and the migration and release patterns of pollutants in the backfill were analyzed in combination with the effluent test results.
2. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 1, characterized in that, The method for determining the size of the tailings backfill sample is as follows: In a hypergravity field with a preset acceleration of ng, the geometric characteristic dimension L of the tailings backfill sample is determined. c The actual size L of the goaf k The following relationship exists between them: L c =L k / n; Where n is the multiple of the supergravity acceleration.
3. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 1, characterized in that, The method for determining the placement height of the Marshall bottle is as follows: the vertical difference between the bottom height of the Marshall bottle's air inlet pipe and the height of the overflow hole is equal to the preset head difference ΔH. The head difference ΔH satisfies the following relationship: ΔH = D × J; Where D is the thickness of the tailings backfill sample, and J is the hydraulic gradient of the goaf.
4. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 1, characterized in that, When checking the airtightness of the model box, the preset height H1 of the Marshall bottle is calculated as follows: H1 = H2 + ΔH; where H2 is the height of the overflow orifice and ΔH is the head difference.
5. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 1, characterized in that, The formula for calculating the permeability coefficient k is as follows: k = V × D / (A × ΔH × t); Where V is the outflow of water from the collection bottle as measured by the first pore pressure gauge, D is the thickness of the tailings backfill sample, A is the cross-sectional area of the tailings backfill sample, ΔH is the head difference, and t is the seepage time.
6. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 1, characterized in that, The tailings in the tailings filling samples were sourced from gold tailings, non-ferrous metal tailings, ferrous metal tailings, red mud, phosphogypsum, or coal gangue.
7. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 1, characterized in that, The tailings backfill samples are cemented backfills, paste-like backfills, paste backfills, non-cemented dry backfills, or backfills modified with additives.
8. The method for assessing the migration of pollutants in tailings backfill bodies according to claim 7, characterized in that, The tailings backfill sample is a cemented backfill, and the cementing material in the cemented backfill is selected from at least one of cement, slag, fly ash, gypsum, lime, and polymer cementitious agents.
Citation Information
Patent Citations
Strip mine backfill groundwater health risk prediction method based on cooperation of GMS and GIS
CN117407944A
Risk assessment method and device for solid waste backfilling
CN119849775A
Harmless treatment and backfill utilization method for high-arsenic-content cyaniding tailings
CN111732223A
Supergravity liquid-solid phase fine multi-stage tailing separation device
CN114178049A